Legal Strength of Speech-Impaired Marriages in Makassar City from the Syafi'i School and KHI Perspectives - Maqsurah, Ainil; Rahman R, Abd.; Muhammad Akmal, Andi (International Journal of Islamic Studies, 2023)
This article discusses the legal strength of speech-impaired marriages in Makassar City from the perspective of the Syafi'i schools and KHI. This article is a Field research using qualitative and descriptive research methods. The source of data in this research is field data in the form of interviews with instructors, those in charge of administration, the celebrant, the speech-impaired bride and the speech-impaired bride's family. The data collection methods used were observation, interviews and documentation. Then, data processing and analysis techniques are carried out through three stages, namely: data reduction, data presentation, and drawing conclusions. The research results show that the legal force for speech-impaired marriages in Makassar City is based on Law Number 1 of 1974 concerning Marriage which regulates marriage provisions. As for marriages with speech impairments, it has been determined in KHI Book I concerning Marriage in Article 17 paragraph (3) and this has compatible with Shafi'i madhhab. Implementation of marriage requirements in Makassar City based on PMA Number 20 of 2019 Article 10 paragraph (2) explains that marriage pillars that have been approved for implementation include the prospective husband, prospective wife, guardian, two witnesses and the consent. This requirement is also stated in KHI book I concerning Marriage Law, Chapter IV concerning the pillars and conditions of marriage, article 14, and then explained in the following articles regarding the requirements and detailed legal explanations. Based on this research, it was found that the terms and conditions were in line with The pillars and conditions that put forward by the Syafi'i school of thought. The practice of marriage contracts taking place in Makassar City refers to the Compilation of Islamic Law article 27 as well as the Regulation of the Minister of Religion of the Republic of Indonesia Number 20 of 2019 article 15. These regulations implemented are in line with several requirements for marriage contracts explained in the Shafi'i school of thought.